2018
DOI: 10.1021/jacs.8b08243
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cotranslational Folding Defects to Membrane Protein Homeostasis

Abstract: Membrane proteins are prone to misfolding and degradation within the cell, yet the nature of the conformational defects involved in this process remain poorly understood. The earliest stages of membrane protein folding are mediated by the Sec61 translocon, a molecular machine that facilitates the lateral partitioning of the polypeptide into the membrane. Proper membrane integration is an essential prerequisite for folding of the nascent chain. However, the marginal energetic drivers of this reaction suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 70 publications
2
67
0
Order By: Relevance
“…S3A) (18). Mutations that promote the formation of these aberrant topomers have been found to decrease the surface expression of rhodopsin (18). A comparison of these putative topological states reveals that the eight C-terminal residues of TM7 (residues 302 to 309) are embedded within the membrane in the native topomer but solvated by water in these two non-native topological states ( fig.…”
Section: Effects Of Mutations On the Energetics Of Coand Posttranslatmentioning
confidence: 99%
See 1 more Smart Citation
“…S3A) (18). Mutations that promote the formation of these aberrant topomers have been found to decrease the surface expression of rhodopsin (18). A comparison of these putative topological states reveals that the eight C-terminal residues of TM7 (residues 302 to 309) are embedded within the membrane in the native topomer but solvated by water in these two non-native topological states ( fig.…”
Section: Effects Of Mutations On the Energetics Of Coand Posttranslatmentioning
confidence: 99%
“…Rhodopsin binds its retinal cofactor with an estimated K d (dissociation constant) of 25 pM (27), and the stabilization afforded by the thermodynamic coupling between binding and folding is known to enhance the cellular expression of rhodopsin (28). However, topological defects in TM7 prevent the formation of the native retinal binding pocket (18). As a result, the stabilization afforded by retinal binding cannot compensate for the proteostatic effects of mutations that disrupt the topology of TM7 (18).…”
Section: Asymmetric Influence Of Retinal On the Surface Expression Ofmentioning
confidence: 99%
“…TMDs of WRB that slowly flips into the ER lumen efficiently assemble with CAML. Previous studies 438 have shown that a charged residue in a TMD of membrane protein is often required for making an 439 ionic bond with an opposite charge in the partner TMD of membrane protein (Cosson et al, 1991;440 Feige and Hendershot, 2013; Roushar et al, 2019). Our data suggest that charged residues in TMDs 441 may also be evolved to interact with membrane protein holdases, thus allowing efficient assembly 442 with partner TMDs.…”
Section: Discussion 391mentioning
confidence: 75%
“…Chimeric Lep proteins were generated by in vitro translation as was described previously. 45 Briefly, mRNA for each chimeric Lep protein was produced from plasmids using the RiboMAX RNA production system in accordance with the manufacturer's instructions (Promega, Madison, WI). Lep proteins were then produced from mRNA by in vitro translation using rabbit reticulocyte lysate (Promega, Madison, WI) supplemented with canine pancreatic rough microsomes (tRNA probes, College Station, TX) and EasyTag 35 S methionine (PerkinElmer, Waltham, MA).…”
Section: In Vitro Translation Of Chimeric Lep Proteinsmentioning
confidence: 99%